LITERATURE STUDY: WASTE EDUCATION IN ELEMENTARY SCHOOL - Ucok Nugroho; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The habit of Indonesian people who are less wise in dealing with their waste is one proof of their low character about waste. Character can be formed through a repetitive behavior obtained through the education process. One of the scopes of education is school. This research aims to find out what the implementation of waste education is like in the scope of elementary school education in Indonesia. This research uses qualitative research methods with literature studies. The data collection technique uses documentation techniques listed in the bibliography. The research data sources come from written texts such as articles, journals, books, news and documents relevant to the study in this research. The results of this study show that the implementation of waste education in elementary schools in Indonesia is carried out with P5 projects, celebration activities, school culture activities, and socialization programs. The obstacles faced are related to the lack of coordination between teachers, schools, parents and students. hopefully this research can make a more coordinated and integrated picture of the implementation of waste education in schools.